Analisis Anggaran Pendapatan dan Belanja Desa Terhadap Pembangunan Desa di Desa Parbuluan VI Kab. Dairi - Tambunan, Adam; Rizki, Atika; Rahmadhani, Sari Nuzullina (Universitas Medan Area, 2022)
This study aims to determine the process of preparing the Village Revenue and Expenditure Budget (APBDes) in Parbuluan VI Village, Parbuluan District, Dairi Regency and to determine the realization of the Village Revenue and Expenditure Budget (APBDes) in the development of Parbuluan VI Village, Parbuluan District, Dairi Regency. This study uses a descriptive method with a quantitative approach with data analysis techniques obtained from analysis of budget reports and budget realizations in Parbuluan VI Village, Parbuluan District, Dairi Regency, North Sumatra Province as well as interviews with related village officials. The results showed that the APBDes preparation process was carried out starting from the RKPDes preparation process until ending with the determination of the budget carried out by the relevant Regency parties and the realization of the budget had been carried out entirely and it was found that there was more budget in each budget period.